2012
DOI: 10.1161/circep.112.971200
|View full text |Cite
|
Sign up to set email alerts
|

Does Location of Epicardial Adipose Tissue Correspond to Endocardial High Dominant Frequency or Complex Fractionated Atrial Electrogram Sites During Atrial Fibrillation?

Abstract: Background— Although increased epicardial adipose tissue (EAT) volume is known to be associated with increased prevalence of atrial fibrillation (AF), the exact mechanisms are unclear. Therefore, we investigated whether EAT locations were associated with high dominant frequency (DF) sites or complicated fractionated atrial electrogram sites during AF. Methods and Results— Three-dimensional reconstruction computed tomography images depicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 28 publications
4
68
1
5
Order By: Relevance
“…10 In addition, serial research efforts have been dedicated to the exploration of the biological mechanisms that relate EAT and AF. 9,3032 These mechanisms include: the actions of proinflammatory cytokines and the adipo-fibrokines released from EAT, such as activin A, which can induce fibrotic changes of the atrial myocardium; adipocyte infiltration of the atrial myocardium, which can cause blockage of local conduction and promote the micro-reentry circuit; and potential modulations of the autonomic nervous system by the ganglionic plexus within the EAT, which may influence the occurrence of AF. In this study, we comprehensively assessed the relationship between the periatrial EAT, the functional properties of the LA, and the circulatory stasis of LAA with contrast-enhanced MDCT and found that the amount of EAT around the LA was independently associated with AF-related stroke, based on a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, serial research efforts have been dedicated to the exploration of the biological mechanisms that relate EAT and AF. 9,3032 These mechanisms include: the actions of proinflammatory cytokines and the adipo-fibrokines released from EAT, such as activin A, which can induce fibrotic changes of the atrial myocardium; adipocyte infiltration of the atrial myocardium, which can cause blockage of local conduction and promote the micro-reentry circuit; and potential modulations of the autonomic nervous system by the ganglionic plexus within the EAT, which may influence the occurrence of AF. In this study, we comprehensively assessed the relationship between the periatrial EAT, the functional properties of the LA, and the circulatory stasis of LAA with contrast-enhanced MDCT and found that the amount of EAT around the LA was independently associated with AF-related stroke, based on a multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…19 A neural mechanism of AF has also been described. In patients with AF high dominant frequency sites corresponded to EAT presence 60 . EAT volumes were higher in patients with permanent AF as opposed to paroxysmal AF.…”
Section: Possible Mechanismsmentioning
confidence: 95%
“…In patients with AF, epicardial adipose tissue has been demonstrated to have increased inflammatory activity on 18-fluorodeoxyglucosepositron emission tomography compared with controls 104 and may also be implicated in the autonomic stimulation of the atria resulting in the triggering and maintenance of AF. 105 Pericardial fat volume has been highly associated with paroxysmal and persistent AF independent of age, LA size, hypertension, sex, valvular heart disease, LV ejection fraction, diabetes mellitus, and body mass index ( Figure 9). 106 Furthermore, total epicardial adipose volume and thickness have both been associated with LA volume.…”
Section: Epicardial Adipose Tissuementioning
confidence: 99%